Influence of Local Real Income, General Allocation Funds, And Specific Allocation Funds on Economic Growth (Empirical Study of Regency / City Government Throughout Java and Bali in 2017) - Kristiyanti; Rukmini; Budiyono; Pardanawati , Laksmi; Kusuma, Indra Lila (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to analyse the influence of regional real income, General Allocation Fund, Special Allocation Fund on Economic Growth. Factors tested in this study are the influence of Local Real Income, General Allocation Funds, Special Allocation Funds as an independent variable while Economic Growth as the dependent variable. The population in this research is all regencies in Java and Bali in 2017 consisting 120 regencies / cities, the sample in this study consisted 116 regencies / cities. The analytical tool used is multiple linear analysis at a significant level 5%. Result of multiple linear analysis is the local income or income variable influences Economic Growth, while the General Allocation Fund variable does not affect Economic Growth and for the Special Allocation Fund variable also does not affect Economic Growth. Hypothesis research results indicate that the Local Real Income, the General Allocation Fund, and the Special Allocation Fund jointly affect the Economic Growth.